2021
DOI: 10.1016/j.cub.2021.07.063
|View full text |Cite
|
Sign up to set email alerts
|

The 3D architecture and molecular foundations of de novo centriole assembly via bicentrioles

Abstract: Highlights d Centrioles assemble de novo via bicentrioles in P. patens d Bicentrioles have two inversely twisted centrioles connected by the cartwheel d Sister centrioles mature asymmetrically and contain long naked cartwheels d SAS6, Bld10, and POC1 are required for cartwheel and centriole assembly, respectively

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…It will be interesting in the future to analyse in depth the 3D structure of Plasmodium BBs and their components, for example, by using these BB and mitotic spindle markers and correlative light and electron microscopy (CLEM) as described recently for the bryophyte Physcomitrium ( Pereira et al, 2021 ). In a recent study, Raspa and Brochet have used expansion microscopy to study the MTOC structures showing its bipartite architecture in Plasmodium ( Rashpa & Brochet, 2022 ), complementing our findings by live cell imaging, super resolution, and EM.…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting in the future to analyse in depth the 3D structure of Plasmodium BBs and their components, for example, by using these BB and mitotic spindle markers and correlative light and electron microscopy (CLEM) as described recently for the bryophyte Physcomitrium ( Pereira et al, 2021 ). In a recent study, Raspa and Brochet have used expansion microscopy to study the MTOC structures showing its bipartite architecture in Plasmodium ( Rashpa & Brochet, 2022 ), complementing our findings by live cell imaging, super resolution, and EM.…”
Section: Discussionmentioning
confidence: 99%
“…In ultrastructural analyses, abnormal BBs were observed in the Mp bld10 mutant, and electron‐dense materials were observed instead of BBs in the Pp bld10 mutant, as reported by Gomes Pereira et al . (2021). These lines of evidence suggest strongly that MpBLD10 and PpBLD10 are BB proteins that function in BB assembly.…”
Section: Discussionmentioning
confidence: 99%
“…BBs of hornworts are monomorphic, and located parallel to each other. Liverworts and mosses possess dimorphic BBs located at staggered positions; the anterior basal body (ABB) is formed at the right side and posterior basal body (PBB) is located at the left side when viewed from the anterior side of the spermatozoid (Figs 2a, 3a) with distinctive angles specific to species (Carothers & Kreitner, 1968; Renzaglia et al ., 1985; Bernhard & Renzaglia, 1995; Carothers et al ., 1997; Gomes Pereira et al ., 2021). Although thorough morphological studies have been conducted, the molecular and genetic players in streptophyte spermatogenesis, including key factors acting in the BB arrangement in bryophytes, remain to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The “bicentriole” is composed of two centrioles sharing a single elongated cartwheel structure. The two centrioles subsequently separate and serve as the basal bodies forming the two flagella ( Moser and Kreitner, 1970 ; Perkins, 1970 ; Robbins, 1984 ; Gomes Pereira et al, 2021 ). Similarly, multiple centrioles form de novo through electron-dense structures termed blepharoplasts in plants such as ferns and cycads during the generation of multiciliated sperms ( Mizukami and Gall, 1966 ; Hepler, 1976 ).…”
Section: De Novo Centriole Formation Naturally Occurs In Var...mentioning
confidence: 99%
“…In the multiciliated cells of planarians, de novo centriole amplification requires the planarian homologs of Plk4, Cep152, CPAP, STIL and SAS-6, the conserved core proteins for centriole assembly ( Azimzadeh et al, 2012 ; Li et al, 2020 ). A recent study involving the bryophyte Physcomitrium patens revealed that the evolutionarily conserved centriole proteins SAS-6, Bld10 (Cep135), and POC1 are required for bicentriole-mediated de novo centriole biogenesis ( Gomes Pereira et al, 2021 ). These results suggest that a common molecular mechanism may be used for centriole formation in a wide range of species.…”
Section: De Novo Centriole Formation Naturally Occurs In Var...mentioning
confidence: 99%